Simultaneous aerobic denitrification and antibiotics degradation by strain Marinobacter hydrocarbonoclasticus RAD-2. (October 2020) - Ruan, Yunjie; Kumar Awasthi, Mukesh; Cai, Lei; Lu, Huifeng; Xu, Xiangyang; Li, Wenbing
Graphical abstract: Highlights: Aerobic denitrification and antibiotics degradation was gained in strain RAD-2. No significant influence on denitrification performance with antibiotics shock. Insignificant inhibiting effect on strain growth under antibiotics dosage. Antibiotics triggered significant time-lapse up-regulation of denitrifying genes. Less N2 O productions were founded in denitrification process with antibiotics. Abstract: Simultaneous denitrification and antibiotics (oxytetracycline, OTC and ciprofloxacin, CFX) degradation was evaluated using a typical aerobic denitrifying strain Marinobacter hydrocarbonoclasticus RAD-2. There was no significant influence on the aerobic nitrate removal efficiency of strain RAD-2 in the presence of these two antibiotics. Along with denitrification, the average degradation rate of 2.92 μg OTC L −1 h −1 was achieved, while no degradation was observed for CFX. The growth behavior indicated that an insignificant inhibition effect could have occurred at an antibiotics dosage lower than 300 μg/L. The transcriptional results revealed that antibiotics exposure caused (<2h) down-regulation of the denitrifying related genes, but triggered a significant subsequent up-regulation (4 h). Less nitrous oxide productions were observed in both aerobic and anoxic denitrification processes with antibiotics. Overall, the hormesis effect caused by antibiotics exposure indicated a potential approach to enhance the co-metabolism degradation performance for nitrate and antibiotics in aerobic denitrification.